2021
DOI: 10.1186/s13148-021-01021-9
|View full text |Cite
|
Sign up to set email alerts
|

SMYD3: a regulator of epigenetic and signaling pathways in cancer

Abstract: Chromatin modifiers and their implications in oncogenesis have been an exciting area of cancer research. These are enzymes that modify chromatin via post-translational modifications such as methylation, acetylation, sumoylation, phosphorylation, in addition to others. Depending on the modification, chromatin modifiers can either promote or repress transcription. SET and MYN-domain containing 3 (SMYD3) is a chromatin modifier that has been implicated in the development and progression of various cancer types. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 83 publications
(115 reference statements)
1
33
0
Order By: Relevance
“…SMYD3 promotes tumour cell migration and invasion by strengthening epithelial-mesenchymal cells and enhancing telomerase activity during the cell cycle [ 44 47 ]. Furthermore, SMYD3 expression is a key risk factor for esophageal [ 47 ], breast [ 46 ], bladder [ 48 ], and other [ 49 ] cancers. A recent study indicated that AP2M1 was overexpressed in adenoid cystic and mucoepidermoid carcinomas and could serve as a prognostic marker of hepatocellular carcinoma [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…SMYD3 promotes tumour cell migration and invasion by strengthening epithelial-mesenchymal cells and enhancing telomerase activity during the cell cycle [ 44 47 ]. Furthermore, SMYD3 expression is a key risk factor for esophageal [ 47 ], breast [ 46 ], bladder [ 48 ], and other [ 49 ] cancers. A recent study indicated that AP2M1 was overexpressed in adenoid cystic and mucoepidermoid carcinomas and could serve as a prognostic marker of hepatocellular carcinoma [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…SMYD3 is a lysine HMT that functions as a transcriptional potentiator of genes by multiple possible mechanisms including binding to specific DNA sequences (5’-CCCTCC-3’ or 5’-GGAGGG-3’), interacting with transcription factors and trimethylated H3K4 (the fourth lysine of histone 3) tails and so on [ 12 ]. Upregulation of SMYD3 has been identified in several types of cancer, such as breast and colorectal cancer, and is associated with tumor proliferation and metastasis [ 13 , 14 ]. These findings imply that SMYD3 might play a crucial role in tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…In the surrogate intrinsic breast cancer subtypes (e.g., luminal A, luminal B, basal, and HER2 + ; TCGA, 2012) and in other TNBC subtypes, high ANKHD1 expression was significantly associated with or showed a tendency to associate with better RFS (Supporting Information: Figure 5). Among the best‐characterized interactors of ANKHD1 regarding clinical impact (Andrade et al, 2017; Bernard et al, 2021; Calses et al, 2019; Zhou et al, 2019), SMYD3 (Supporting Information: Figure 6), but not YAP1 (Supporting Information: Figure 7), had a similar profile to ANKHD1 in the clinical outcome of patients with breast cancer.…”
Section: Resultsmentioning
confidence: 94%
“…Survival curves were estimated using the Kaplan-Meier method, and the hazard ratio (HR), 95% confidence interval, and p values are indicated in the graphs. best-characterized interactors of ANKHD1 regarding clinical impact (Andrade et al, 2017;Bernard et al, 2021;Calses et al, 2019;Zhou et al, 2019), SMYD3 (Supporting Information: Figure 6), but not YAP1 (Supporting Information: Figure 7), had a similar profile to ANKHD1 in the clinical outcome of patients with breast cancer.…”
Section: Ankhd1 Mrna Expression Correlates With Breast Cancer Patient...mentioning
confidence: 96%